2010
DOI: 10.1002/hyp.7788
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the deep seepage component of the hillslope and catchment water balance within a measurement uncertainty framework

Abstract: Abstract:Deep seepage is a term in the hillslope and catchment water balance that is rarely measured and usually relegated to a residual in the water balance equation. While recent studies have begun to quantify this important component, we still lack understanding of how deep seepage varies from hillslope to catchment scales and how much uncertainty surrounds its quantification within the overall water balance. Here, we report on a hillslope water balance study from the H. J. Andrews Experimental Forest in Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 62 publications
3
73
1
Order By: Relevance
“…The time period used is important if signatures are used for catchment classification: an unusual event such as a large flood may shift the signature values (Casper et al, 2012). Additional uncertainty sources can be important in other catchments, such as catchment boundary uncertainty and flow bypassing the gauge (Graham et al, 2010a).…”
Section: Methods Limitations and Future Developmentsmentioning
confidence: 99%
“…The time period used is important if signatures are used for catchment classification: an unusual event such as a large flood may shift the signature values (Casper et al, 2012). Additional uncertainty sources can be important in other catchments, such as catchment boundary uncertainty and flow bypassing the gauge (Graham et al, 2010a).…”
Section: Methods Limitations and Future Developmentsmentioning
confidence: 99%
“…As a consequence of the lower bypass estimate by Graham et al (2010), they estimated higher deep seepage fractions. However, our simulated bedrock seepage is consistent with the estimated deep seepage at the catchment scale by Graham et al (2010) that was on average approximately 21 % of precipitation at steady state. Our modeling approach of bedrock seepage (with no later exfiltration of bedrock water) is largely in agreement with the study of Gabrielli et al (2012) at the same hillslope.…”
Section: Process Understanding Through the Hillvi Modelmentioning
confidence: 99%
“…Graham et al (2010) showed that deep seepage at the WS10 hillslope scale was 48 ± 35 % of applied water during the same irrigation period (calculated after 10 days of drainage) based on water balance calculations. Our modeling results (Model 2) showed that bedrock seepage accounted for 24 and 26 % based on total applied water and δ 2 H mass of the labeled pulse, respectively.…”
Section: Process Understanding Through the Hillvi Modelmentioning
confidence: 99%
See 2 more Smart Citations